2016
DOI: 10.1055/s-0035-1569374
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated with Higher Pro-Inflammatory Tumor Necrosis Factor-α Levels in Young Women with Type 1 Diabetes

Abstract: Aims While cytokines play a role in the etiology of type 1 diabetes, cytokines later in the disease are less understood. We therefore investigated associations of pro-inflammatory tumor necrosis factor-α levels measured at prolonged disease duration with C-peptide at diagnosis, long-term glycemic control, diabetes duration, clinical factors, and health behaviors. Methods Data and blood were collected during an ancillary study to the longitudinal Wisconsin Diabetes Registry, a population-based cohort followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In the LEW.1AR1‐ iddm rat animal model of T1D, treatment with anti‐TNFα only in combination with anti‐ T‐cell receptor antibodies restored normoglycemia, normalized C‐peptide and increased beta‐cell proliferation 36 . Furthermore, T1D patients studies identified increased TNFα plasma concentration associated with higher HbA1c 37 and lower C‐peptide levels 38 . In accordance, we found TNFα‐dominant T MEM responses especially at long‐term T1D stage.…”
Section: Discussionsupporting
confidence: 81%
“…In the LEW.1AR1‐ iddm rat animal model of T1D, treatment with anti‐TNFα only in combination with anti‐ T‐cell receptor antibodies restored normoglycemia, normalized C‐peptide and increased beta‐cell proliferation 36 . Furthermore, T1D patients studies identified increased TNFα plasma concentration associated with higher HbA1c 37 and lower C‐peptide levels 38 . In accordance, we found TNFα‐dominant T MEM responses especially at long‐term T1D stage.…”
Section: Discussionsupporting
confidence: 81%
“…A pro-inflammatory environment can increase MMP expression which has been implicated in impaired wound healing in both T2DM and animal models of diabetic skin 24,38,39 . Furthermore, in a pro-inflammatory environment, increased activity of MMPs has been shown to impair dermal fibroblast migration 15,20,40 . Therefore, we sought to establish whether there was a difference in expression and activity of MMPs and TIMPS between ND-DF and T2DM-DF, or their responses to TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, excessive and extensive exposure may contribute to chronic non-healing wounds prevalent in T2DM. Circulating plasma levels of TNF-α are typically around 10 pg/ml 18 but in diabetic patients can be almost tenfold higher 19 and circulating TNF-α concentrations positively correlate with diabetes duration 20 . In healthy skin tissue, concentrations of TNF-α are highly variable but typically in the order of 1.5 ng/ml 21 .…”
mentioning
confidence: 99%